IMPLIKASI PEMBERIAN GAJI DAN INSENTIF TERHADAP KINERJA KARYAWAN PERUMDA BPR BANK BREBES - Afridah, Nur; Wibowo, Wahyu; Syaifulloh, Muhammad; Riono, Slamet Bambang (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Employment is a very basic aspect of human life because it includes social and economic dimensions. Because in human resources performance issues need to be explored in order to be able to improve performance in accordance with company expectations, therefore the factors that influence it are needed. This study aims to determine the effect of salary and incentives on the performance of Perumda BPR Bank Brebes employees. The population and sample in this study were 74 with the census method, the data collection technique was by dividing the questionnaire, while the data analysis technique used SPSS with Hypothesis Testing carried out on significance. a = 0.05. The results of the study show that the provision of salaries and incentives has an effect on employee performance by 12.9% .